Questions for In-Depth Reflection and Improvement of Music Teaching (Appendix to Chapters 20−29) - Kovačič, Bojan (Širjenje obzorij o poučevanju glasbe, 2025)
This chapter presents a series of questions based on the ten chapters of the monograph (Chapters 20−29): Methods of Using Music and The Bass Guitar in Teaching, Developing Auditory Perception and Musical Skills, Folk Dances as a Means of Cultural Awareness, Developing Motor Skills through Dance, Movement with Music, Use of Orff Instruments in Musical Education, Creating with Orff instruments, Listening to Classical Music, Listening to Music as a Means of Relaxation and Concentration, and Musical Preferences of Pupils. The questions are divided into four areas (lesson planning, lesson delivery, observation and evaluation, improvement and development) and enable teachers and students to reflect more closely on their own teaching practise.